PENGARUH EFIKASI DIRI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT PERMODALAN NASIONAL MADANI (PNM) MEKAAR AREA BEKASI 3 - Cahyaning Dumilah, Tri; Made Aryata, I (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to find out how much the influence of self-efficacy and work motivation on employee performance at PT Permodalan Nasional Madani (PNM) MEKAAR Area Bekasi 3, both partially and simultaneously. This research uses a quantitative method with a population of 146 employees and a sample of 60 respondents, determined using a simple random sampling technique based on the Slovin formula with a significance level of 10%. Data analysis includes validity, reliability, classical assumption tests, multiple linear regression, correlation coefficient, coefficient of determination, and hypothesis testing using SPSS version 26. Based on the analysis results, the regression equation obtained is Y = 8.329 + 0.306X₁ + 0.525X₂, which means that self-efficacy (X₁) and work motivation (X₂) have a positive effect on employee performance (Y). The coefficient of determination shows that, simultaneously, self-efficacy and work motivation contribute 66.2% to employee performance, while the remaining 33.8% is influenced by other factors. The partial test (t-test) results show that self-efficacy has a significant effect on employee performance with a t-value of 7.022 > t-table of 2.002 and a significance value of 0.000 < 0.05. Similarly, work motivation has a significant effect on employee performance with a t-value of 9.412 > t-table of 2.002 and a significance value of 0.000 < 0.05. The simultaneous test (F-test) results show an F-value of 55.719 > F-table of 3.16 with a significance value of 0.000 < 0.05, indicating that self-efficacy and work motivation together have a significant effect on employee performance at PT Permodalan Nasional Madani (PNM) MEKAAR Area Bekasi 3